More second-order than ever? : The 2014 european election in Portugal - Freire, André (2016)
Citation information: the chapters of this book were originally published in South European Society and Politics. volume 20, issue 3 (September 2015). When citing this material, please use the original page numbering for the article: Freire, A. & Santana-Pereira, J. (2015). More Second-Order than Ever? The 2014 European Election in Portugal. South European Society and Politics, 20(3), 381-401